Efficacy and surgical procedures of preoperative splenic artery embolization for laparoscopic splenectomy of a massive splenomegaly: A case report. (2015) - Nitta, Toshikatsu; Fujii, Kensuke; Kawasaki, Hiroshi; Takasaka, Isao; Kawata, Shuhei; Onaka, Masahiko; Ishibashi, Takashi
Highlights: The combination of embolization of the splenic artery and continuous epinephrine infusion to reduce the spleen volume was highly effective. New technique of laparosopic splenolectomy for massive splenomegaly. Spleen volume started to decrease immediately after the onset of intravenous infusion of low-dose epinephrine. Abstract: Here, we describe the case of a 58-year-old woman diagnosed with massive splenomegaly with a malignant lymphoma that had a maximum diameter of 24 cm. Splenectomy was indicated because of thrombocytopenia and abdominal distention. Therefore, a balloon catheter was inserted preoperatively through the splenic artery for embolization and continuous infusion to reduce the spleen volume. It enabled easy handling of the spleen and minimized bleeding. The volume of the spleen was estimated at 1896 g through the skin incision, as measured by volumetric computed tomography; thus, laparoscopy seemed difficult. However, the surgery was successfully performed only with laparoscopic surgery, and the volume of the resected spleen was 1020 g. This preoperative preparation is an effective alternative to laparoscopic removal of a huge splenomegaly.